2017
DOI: 10.21595/vp.2017.18958
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of selected vibroacoustic signals recorded on EMU vehicle running on chosen routes under supervised operating conditions

Abstract: Abstract. The subject matter of the paper is an analysis of the results of acceleration signals measurement obtained from the prototype of Rail Vehicle and Rail Track Monitoring System. The prototype of the system measures acceleration signals on some elements of electric multiple unit, such as bogie frames, wheels and railway vehicles body. The results of measurement were converted to values of statistical parameters, e.g.: an amplitude, a root mean square, a kurtosis coefficient, an interquartile range. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Both equalities (6)- (8) and our experimental research demonstrate that by means of the equivalent samples of the noise " ( ∆ ), we can obtain results that are identical to the results of the analysis of the same vibration signals with known real samples of the noise ( ∆ ). To this end, we use the formula (10) to determine the equivalent samples " ( ∆ ) of the useful vibration signal ( ∆ ).…”
Section: Algorithms For Analysis Of Noisy Vibration Signals Using Equsupporting
confidence: 68%
See 2 more Smart Citations
“…Both equalities (6)- (8) and our experimental research demonstrate that by means of the equivalent samples of the noise " ( ∆ ), we can obtain results that are identical to the results of the analysis of the same vibration signals with known real samples of the noise ( ∆ ). To this end, we use the formula (10) to determine the equivalent samples " ( ∆ ) of the useful vibration signal ( ∆ ).…”
Section: Algorithms For Analysis Of Noisy Vibration Signals Using Equsupporting
confidence: 68%
“…Intelligent system of noise control of the technical condition of railroad tracks 69. (8) Numerous computational experiments have shown that despite possible deviations of the approximate values of the equivalent samples " ( ∆ ) from their true values ( ∆ ) by the value ∆ ( ∆ ) = " ( ∆ ) − ( ∆ ), the following equality takes place between their estimates:…”
Section: Algorithms For Analysis Of Noisy Vibration Signals Using Equmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, road irregularities represent undesirable effects, which come to a human body through tyres, a suspension system, a seat cushion etc. Then, they influence vibration properties of a vehicle mechanical system [12,18,20,25].…”
Section: Mbs Model Of a Vehiclementioning
confidence: 99%
“…Generally, road irregularities represent undesirable effects, which come to a human body through tyres, a suspension system, a seat cushion etc. Then, they influence vibration properties of a vehicle mechanical system [17,18,19].…”
mentioning
confidence: 99%